Effect of the prevalence of ectoparasites in the behavioral patterns of wild vicuñas (vicugna vicugna) - Arzamendia, Yanina (2012)
The vicuña (Vicugna vicugna) is a wild South American camelid adapted to high Andean arid environments that almost became extinct due to overharvest for their fleece. Nowadays, the increase in their populations is generating conflicts with villagers, who consider vicuñas as transmitters of ectoparasites (mainly mites) to livestock. Nevertheless, information concerning this issue is scarce, despite the importance of vicuñas and their close phylogenetic relationship with domestic camelids (Lama glama and Vicugna pacos). We surveyed ectoparasites in wild population of vicuñas (Vicugna vicugna) and some llamas (Lama glama) from the Pozuelos Biosphere Reserve, Argentina from 1999 to 2005. Parasite samples were collected directly from skin examination and scrapings. The prevalence of ectoparasites detected in identified vicuñas was 2.44% for sucking louse Microthoracius mazzai, M. praelongiceps and Sarcoptes scabiei, which also may infect llamas. Behaviour of vicuñas with louse infestation and sarcoptic mange lesions did not differ from those with no clinical signs. The objectives of this study were to determine the presence and prevalence of mange and lice in a wild population of the southern vicuña subspecies (V. vicugna vicugna) from Cieneguillas, Jujuy and their effect on the behavioural patterns of the species.